A novel and efficient one-pot synthesis of symmetrical diamide (bis-amidate) prodrugs of acyclic nucleoside phosphonates and evaluation of their biological activities - Jansa, Petr; Baszczyňski, Ondřej; Dračínský, Martin; Votruba, Ivan; Zídek, Zdeněk; Bahador, Gina; Stepan, George; Cihlar, Tomas; Mackman, Richard; Holý, Antonín; Janeba, Zlatko (European journal of medicinal chemistry, 2011)
A novel and efficient method for the one-pot synthesis of diamide (bis-amidate) prodrugs of acyclic nucleoside phosphonates, starting from free phosphonic acids or phosphonate diesters is reported. The approach from phosphonate diesters via their bis(trimethylsilyl) esters is highly convenient, eliminates isolation and tedious purification of the phosphonic acids, and affords the corresponding bis-amidates in excellent yields (83-98%) and purity. The methodology has been applied to the synthesis of the potent anticancer agent GS-9219, and symmetrical bis-amidates of other biologically active phosphonic acids. Anti-HIV, antiproliferative, and immunomodulatory activities of the compounds are discussed including the bis-amidate prodrugs 14 and 17 that exhibited anti-HIV activity at submicromolar concentrations with minimal cytotoxicity.
Keywords: Animals; proliferace buněk; buněčné linie; Prodrugs; diamid; Adjuvants, Immunologic; Anti-HIV Agents; Nucleosides; lidé; Mice; prekurzory léčiv; Drug Evaluation, Preclinical; nukleosidy; myši; Cell Line; hmotnostní spektrometrie s elektrosprejovou ionizací; magnetická rezonanční spektroskopie; preklinické hodnocení léčiv; organofosfonáty; Cell Proliferation; Diamide; látky proti HIV; zvířata; Magnetic Resonance Spectroscopy; Mice, Inbred C57BL; Spectrometry, Mass, Electrospray Ionization; adjuvancia imunologická; Organophosphonates; myši inbrední C57BL; Humans